2020
DOI: 10.1111/fwb.13603
|View full text |Cite
|
Sign up to set email alerts
|

Community isolation drives lower fish biomass and species richness, but higher functional evenness, in a river metacommunity

Abstract: 1. The flow of individuals among communities and their interactions with local environmental filters are increasingly recognised as determinants of biodiversity patterns in riverine ecosystems. Both incoming dispersers and local conditions are expected to systematically change along connectivity gradients from headwaters to downstream communities. However, the interplay between isolation-centrality gradients and environmental conditions as determinants of biodiversity structure and function has seldom been con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 108 publications
(249 reference statements)
3
25
1
Order By: Relevance
“…Although some studies have shown that within-assemblage abundance increases in downstream direction (Henriques-Silva et al 2019;Borthagaray et al 2020), we found a negative relationship between abundance and distance from headwaters. This was due to that three of the most abundant species (Serrapinnus cf.…”
Section: Effect Of Environmental and Spatial Factors On Fish Assemblagescontrasting
confidence: 96%
See 1 more Smart Citation
“…Although some studies have shown that within-assemblage abundance increases in downstream direction (Henriques-Silva et al 2019;Borthagaray et al 2020), we found a negative relationship between abundance and distance from headwaters. This was due to that three of the most abundant species (Serrapinnus cf.…”
Section: Effect Of Environmental and Spatial Factors On Fish Assemblagescontrasting
confidence: 96%
“…Small fish are mostly short-distance migrants, and respond mainly to fine-scale environmental variations like water depth and habitat structure (Lamouroux et al 1999;Fernandes et al 2015). Likewise, the effect of the distance from headwaters also points to limited dispersal capacity, as predicted by the network position hypothesis (Henriques-Silva et al 2019;Borthagaray et al 2020). Environmental and spatial factors explained only 30% of the variation in our data, which indicates that important variables, such as functional connectivity, and ecological interactions, such as competition, known to be important in regulating composition and structure of local assemblages (Cadotte and Tucker 2017) were not considered.…”
Section: Effect Of Environmental and Spatial Factors On Fish Assemblagesmentioning
confidence: 99%
“…As all TRs were flooded during the same rainfall event, the identity of each TR lost relevance against the spatial isolation. The relevance of closeness has already been shown at larger landscape scales when assessing changes in species richness (Borthagaray et al, 2020). Interestingly, here this effect was detected at a smaller spatial scale, highlighting the potential of this metric for explaining diversity patterns in dendritic networks (Economo & Keitt, 2010;Carrara et al, 2012;Altermatt, 2013).…”
Section: Discussionsupporting
confidence: 68%
“…By considering the 'out-closeness' as our centrality metric we assume that a higher closeness value for a given site implies higher isolation (i.e. upstream reaches) within a network (Borthagaray et al, 2020). Closeness provides a solid proxy of dendritic network structure and can relate significantly to biodiversity in river networks at theoretical, experimental, observational and management levels (Estrada & Bodin, 2008;Economo & Keitt, 2010;Altermatt, 2013;Borthagaray et al, 2020).…”
Section: Spatial Connectivitymentioning
confidence: 99%
See 1 more Smart Citation